Mass shootings and civilian armament - Anisin, Alexei (Routledge studies in crime and society, 2022)
"Mass Shootings and Civilian Armament provides the first comprehensive multi-methodological analysis of the relationship between mass shootings and firearm purchases (as proxied by background checks) in the US on national level data from 1999-2020. Interdisciplinary in nature, Mass Shootings and Civilian Armament will not only be of great interest to scholars of Criminology, but will also speak to Sociologists, Economists, Public Policy scholars, Political Scientists, Historians, as well as Cultural Studies and American Studies scholars"--